A UTILIZAÇÃO DO MAPA ESTRATÉGICO DE BALANCED SCORECARD (BSC) COMO FERRAMENTA DE GESTÃO PARA A MELHORIA DA EFICÁCIA OPERACIONAL EM UMA INSTITUIÇÃO DE ENSINO BÁSICO: ESTUDO DE CASO - Mendes, Ana Paula Fernandes (2010)
The aim of this paper is to present a strategic map that enables managers of an institution of Basic Education to identify improvements in processes and results of operations. The investigative question was to ascertain the possibility of implementing a model of Balanced Scorecard (BSC) in this type of institution. We started from the hypothesis that this system may be important management tool that enables improved operational efficiency. Was used as the main theoretical Management System Strategic Kaplan and Norton (2004) that allows to develop an assessment of business performance. The research is a case study of characteristic exploratory, descriptive and explanatory. Questionnaires were applied to a population of 304 individuals. The results correspond to 76.64% of the universe: 233 individuals. The study results show that there is a possibility of implementing a strategic map in Basic Private Education Institution. The findings indicate that the BSC should not be deployed without the commitment of senior management and that clearly defined the strategy and its dissemination are key factors for its implementation. Pedagogical issues are not part of this study.